2019
DOI: 10.3389/fmicb.2019.00735
|View full text |Cite
|
Sign up to set email alerts
|

Opsin 1 and Opsin 2 of the Corn Smut Fungus Ustilago maydis Are Green Light-Driven Proton Pumps

Abstract: In fungi, green light is absorbed by rhodopsins, opsin proteins carrying a retinal molecule as chromophore. The basidiomycete Ustilago maydis , a fungal pathogen that infects corn plants, encodes three putative photoactive opsins, called ops1 (UMAG_02629), ops2 (UMAG_00371), and ops3 (UMAG_04125). UmOps1 and UmOps2 are expressed during the whole life cycle, in axenic cultures as well as in planta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 75 publications
2
47
0
Order By: Relevance
“…The U. maydis strains expressing opsin1 fused to enhanced green fluorescent protein (eGFP) were described in detail before (Panzer et al, 2019) and derived from the wild type isolate FB1 (Banuett and Herskowitz, 1989). Either the strain FB1 UmOps1 P crg ::UmOps1-eGFP K1 or FB1 P crg ::UmOps1-eGFP KA was used for ExM experiments.…”
Section: Fungal Strains / Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…The U. maydis strains expressing opsin1 fused to enhanced green fluorescent protein (eGFP) were described in detail before (Panzer et al, 2019) and derived from the wild type isolate FB1 (Banuett and Herskowitz, 1989). Either the strain FB1 UmOps1 P crg ::UmOps1-eGFP K1 or FB1 P crg ::UmOps1-eGFP KA was used for ExM experiments.…”
Section: Fungal Strains / Cultivationmentioning
confidence: 99%
“…Either the strain FB1 UmOps1 P crg ::UmOps1-eGFP K1 or FB1 P crg ::UmOps1-eGFP KA was used for ExM experiments. U. maydis sporidia were grown as described before (Panzer et al, 2019). Sporidia were grown in PDB for 15-24 h at 28 • C and 100 rpm, harvested by centrifugation (4000 × g, 3 min), washed once in ddH 2 O and resuspended in ddH 2 O to a final density of 6.5 x 10 5 sporidia/mL.…”
Section: Fungal Strains / Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The same strategy was applied for the identification of enzymes of the prenyl phosphate module, producing geranylgeranyl-diphosphate via chain elongation from IPP and DMAPP (GGPP; Figure 1A, Table 1). The carotenoid module has been predicted before and its main function is the production of retinal that serves as chromophore for photoactive opsin channels Ops1-3 (Estrada et al, 2009;Panzer et al, 2019). The cleavage reaction of -carotene into two retinal molecules is catalysed by Cco1 (-carotene cleavage oxygenase; Estrada et al, 2009).…”
Section: U Maydis Contains An Evolutionarily Conserved Fpp Pathwaymentioning
confidence: 99%
“…It was already shown that deletion of cco1 resulted in the accumulation of -carotene (Estrada et al, 2009). Loss of retinal synthesis causes no mutant phenotype under standard growth conditions or during pathogenic development, thus the biological function of opsins in U. maydis is as yet unclear (Estrada et al, 2009;Panzer et al, 2019).…”
Section: U Maydis Contains An Evolutionarily Conserved Fpp Pathwaymentioning
confidence: 99%